Kedudukan Pekerja/Buruh dalam Perkara Kepailitan Ditinjau dari Peraturan Perundang-Undangan dan Teori Keadilan - Susilo Andi Darma (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
This research conducted aimed to know/position worker worker in casebankruptcies reviewed from regulation legislation and theory justice. Creditor insomething case bankruptcies divided into three types namely creditor separatist, preferencreditor, and competitor creditor. worker worker in case bankruptcies at as preferencreditor that mean creditor that have privilege, namely secured by article special law 95 No. verse Law 13 Year 2003 about employment. This position co-located cum right predecessor country that regulated in article 21 Number verse Law 6 year 1983 about Provision Is General and Cara's Order Taxation as has been amended last with Number Law 16 Year 2000. This research is juridical normative research namely research law conducted in a way research material book or secondary data merely. This research conducted with way literature review to get secondary data. Data obtained analyzed by qualitative namely analysis to data obtained and selected based on qualityand the truth as well as possess relationship with research henceforth poured bydescriptive. The result of research and working through namely that/position worker worker in case bankruptcies can be reflected in status working relationship between/worker worker with entrepreneur,/worker worker is holder privilege, not fulfilled by him rights worker is wanprestasi, fall him demand rights worker in bankruptcies,/worker worker have the right retention,/worker worker have the right submit objection letter. And from justice theory side, justice to/position worker worker with special creditor others can materialize if community profess principle of justice that is same or possess frame of reference that is same in case bankruptcies.